ICT Update 67: ICT innovation and the people behind it - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
ICT Update is a bimonthly printed and on-line magazine (http://ictupdate.cta.int) and an accompanying e-mail newsletter published by CTA. This issue focuses on ICT innovation and the people behind it.